“You’ll learn to be the best dad ever!” A parenting app as a digital “more-knowledgeable-other” at the transition to fatherhood - Cino, Davide (Studi sulla Formazione/Open Journal of Education, 2024)
Transition to parenting is a transformative phase where first-time parents may feel the expectation of having to “learn” and “perform” a new social role. In this scenario, parenting apps are part of a broader media ecology new parents can rely on, as pedagogical agents providing informal education and support. This paper offers a critical-pedagogical analysis of a fathering app, investigating the type of parenting knowledge proposed and the broader overarching discourses it reflects. Findings show a double tendency. At a surface level, the app serves the practical purposes of offering new fathers solace and guidance; at a latent level, fatherhood is discursively “intensified”, following intensive parenting trends, and “othered” as a different experience from motherhood, whereas the role of the father is constructed as both ancillary and controlling, reinforcing, besides trying to question, traditional family scripts.